Pain Assessment in Patients during Hemodialysis Treatment: Quality Improvement Project - Rodrigues, Rita (2024)
Pain is a prevalent symptom in patients with chronic kidney disease, related to disease progression, comorbidities, and required immobility during dialysis treatment. Nurses must perform detailed pain assessments to manage pain effectively during hemodialysis treatment. This quality improvement project, reported using SQUIRE 2.0, aims to describe pain characteristics in chronic kidney disease patients in a hemodialysis unit clinic in Portugal, implement strategies to improve the pain assessment process in patients with chronic kidney disease during hemodialysis treatment, and assess nurses’ satisfaction with the implemented strategies. The study was conducted in a Portuguese hemodialysis clinic, with patients and nurses, in three phases: diagnostic study, protocol implementation, and a descriptive study to assess nurse satisfaction. Seventy-five patients (mean age 71 ± 12.6 years) participated, with 64% reporting moderate chronic pain daily and 48% during hemodialysis treatment. Thirteen nurses considered the pain assessment protocol important, rating their satisfaction at 7.92 ± 1.32 (0–10). Standardizing practices through protocol implementation is likely to improve care and increase nurse satisfaction.